2022
DOI: 10.3389/fonc.2022.955505
|View full text |Cite
|
Sign up to set email alerts
|

Impact of physical exercise programs in breast cancer survivors on health-related quality of life, physical fitness, and body composition: Evidence from systematic reviews and meta-analyses

Abstract: BackgroundBreast cancer is the most common cancer worldwide, and despite remarkable progress in its treatment, the survivors’ quality of life is hampered by treatment-related side effects that impair psychosocial and physiological outcomes. Several studies have established the benefits of physical exercise in breast cancer survivors in recent years. Physical exercise reduces the impact of treatment-related adverse events to promote a better quality of life and functional outcomes.AimThis study aims to provide … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
13
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 34 publications
(15 citation statements)
references
References 66 publications
1
13
0
1
Order By: Relevance
“…A review of non‐pharmacological interventions to improve QOL in cancer survivors concluded that PA improves QOL, but few studies assessed outcomes beyond 3 months 35 . The authors also reported that aerobic plus resistance training provided maximum improvements in QOL (also supported by another review 36 ); whereas our interventions focused on aerobic PA. Generally, longer duration programs and those offered with on‐site supervision have larger, positive impact on QOL 36 while our programs were distance‐based and did not provide on‐site supervision.…”
Section: Discussionmentioning
confidence: 71%
See 1 more Smart Citation
“…A review of non‐pharmacological interventions to improve QOL in cancer survivors concluded that PA improves QOL, but few studies assessed outcomes beyond 3 months 35 . The authors also reported that aerobic plus resistance training provided maximum improvements in QOL (also supported by another review 36 ); whereas our interventions focused on aerobic PA. Generally, longer duration programs and those offered with on‐site supervision have larger, positive impact on QOL 36 while our programs were distance‐based and did not provide on‐site supervision.…”
Section: Discussionmentioning
confidence: 71%
“…Generally, longer duration programs and those offered with on-site supervision have larger, positive impact on QOL 36 while our programs were distance-based and did not provide on-site supervision.…”
Section: Resultsmentioning
confidence: 95%
“…In addition to the patient’s age, comorbidities, and perioperative procedures, the survival of patients with breast cancer is influenced by socioeconomic factors, such as the level of education and the availability of health care [ 25 ]. Better physical condition and exercise can contribute to a better quality of life in patients after breast cancer surgery [ 26 , 27 , 28 ]. We, therefore, expected that patients who had better HGS, as well as those in the group with bolus administration of levobupivacaine, could have better long-term survival.…”
Section: Discussionmentioning
confidence: 99%
“…The study findings revealed that resistance training positively affected the strength of the upper and lower body in the specific population under investigation [ 99 ]. The findings from two meta-analyses suggest that participation in physical activity can positively impact HRQoL, cardiorespiratory fitness, and body composition in individuals who have successfully recovered from breast cancer [ 100 , 101 ].…”
Section: Physical Exercises and Breast Cancer Post-treatmentmentioning
confidence: 99%